Modified Soaking Procedure Based Experimental Investigation of Cyclic Gas Recovery: Effect of Gas-Phase Miscibility - Muhend Milad; Rabiaa Omran; Ali Milad; Abdulgader Alsharif (African Journal of Advanced Pure and Applied Sciences, 2023)
The current and latest technology to produce unconventional oil reservoirs is the cyclic gas injection method. Over the last decade, extensive experiments have been conducted to produce tight reservoirs, and a wide variety of parameters have been considered. However, the influence of key factors such as gas-phase miscibility and miscibility mode on oil recovery remains unclear. Additionally, previous studies have focused mostly on conventional procedures that fail to satisfactorily represent depleted oil field conditions. These assumptions may be the justification for the disappointing outcomes of some pilot tests, in spite of the outstanding demonstration of competence of the lab scale. This study attempts to explore the sensitivity of CO2 phase miscibility and CO2 miscibility mode in enhancing the bypassed oil recovery. Prior to the cyclic gas process, oil is bypassed in tight sandstone cores using the immiscible soaking step. The findings indicate that increasing CO2 injection pressure may not be the only factor contributing to extracting residual oil; the CO2 phase properties may also play a significant role in producing remaining oil. The use of supercritical CO2 resulted in the highest bypassed oil recovery rate of up to 30.40%. However, the compressed liquid CO2 phase recovered slightly more initial oil, particularly at pressures less than or equal to the minimum miscibility pressure (MMP). Increasing the CO2 soaking time plays a major role in extracting the bypassed oil. However, 50% of the oil can be extracted within the first cycle. Therefore, a long soaking period is not recommended in the subsequent cycles.